Ribosomal frameshifting requires a pseudoknot in the Saccharomyces cerevisiae double-stranded RNA virus. - Tzeng, T H (1992)
The large double-stranded RNA of the Saccharomyces cerevisiae (yeast) virus has two large overlapping open reading frames on the plus strand, one of which is translated via a -1 ribosomal frameshift. Sequences including the overlapping region, placed in novel contexts, can direct ribosomes to make a -1 frameshift in wheat germ extract, Escherichia coli and S. cerevisiae. This sequence includes a consensus slippery sequence, GGGUUUA, and has the potential to form a pseudoknot 3' to the putative frameshift site. Based on deletion analysis, a region of 71 nucleotides including the potential pseudoknot and the putative slippery sequence is sufficient for frameshifting. Site-directed mutagenesis demonstrates that the pseudoknot is essential for frameshifting.